دراسة العلاقة بين مرض الصدفية ومستويات فيتامين د: دراسة ميدانية داخل بعض عيادات الجلدية بمدينتي العجيلات وصبراتة - نجاح مديهين (Surman Journal of Science and Technology, 2024)
This study aimed to determine the serum levels of vitamin D among patients with psoriasis, to examine the relationship between disease characteristics and vitamin D levels, and to investigate the association between vitamin D levels and disease duration in psoriasis patients. A descriptive analytical study design was employed. The study included 40 patients diagnosed with psoriasis, aged between 18 and 90 years, who attended the dermatology outpatient clinics at the selected centers. All participants were interviewed and clinically examined by specialist physicians. Data were collected using structured questionnaires after obtaining informed consent. Collected variables included demographic and clinical characteristics such as age, sex, occupation, marital status, smoking habits, body mass index (BMI), and family history of psoriasis. The study results showed that the majority of patients (67.5%) had type III psoriasis. A considerable proportion of the sample were smokers (45%). Most participants had a positive family history of the disease (87.5%). Additionally, 75% of the patients reported regular exposure to direct sunlight. More than half of the patients (55%) had a disease duration of less than five years. The highest proportion of patients (35%) had serum vitamin D levels ranging between 5–10 ng/mL, which is below the established normal range. This study did not identify a clear causal relationship between psoriasis and reduced serum vitamin D levels.